2021
DOI: 10.1111/hsc.13413
|View full text |Cite
|
Sign up to set email alerts
|

A systematic scoping review of community‐based interventions for the prevention of mental ill‐health and the promotion of mental health in older adults in the UK

Abstract: Background: Mental health concerns in older adults are common, with increasing age-related risks to physical health, mobility and social isolation. Community-based approaches are a key focus of public health strategy in the UK, and may reduce the impact of these risks, protecting mental health and promoting wellbeing. We conducted a review of UK community-based interventions to understand the types of intervention studied and mental health/wellbeing impacts reported. Method:We conducted a scoping review of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 73 publications
2
16
0
1
Order By: Relevance
“…We found that, regardless of tenure, those who reported insufficient social contact (IC7) had markedly poorer mental wellbeing, demonstrating the need for more public health interventions addressing social isolation and loneliness. There are a number of person-centred interventions that can be adopted, such as volunteering, to improve health outcomes; however, more robust evidence of effectiveness among those experiencing social isolation is needed [ 57 , 58 ]. Overall, our findings support ‘connecting with people’ as one of the ‘five ways to wellbeing’, as promoted by the NHS [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that, regardless of tenure, those who reported insufficient social contact (IC7) had markedly poorer mental wellbeing, demonstrating the need for more public health interventions addressing social isolation and loneliness. There are a number of person-centred interventions that can be adopted, such as volunteering, to improve health outcomes; however, more robust evidence of effectiveness among those experiencing social isolation is needed [ 57 , 58 ]. Overall, our findings support ‘connecting with people’ as one of the ‘five ways to wellbeing’, as promoted by the NHS [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The United Kingdom proposed a ten-year plan for the integration of national services for older adults [ 38 ]. The goal of this plan is to eliminate discrimination against the elderly, promote the health and independence of the elderly, and meet the health needs of the elderly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the current evidence base for effectiveness and cost-effectiveness of community-based interventions is limited [39,40]. For example, the wide range of interventions and outcome measures for older adults, confounds a clear understanding of what works [41]. While some interventions have shown promise for adults of working age, such as workplace-based stress management [42], co-located welfare advice [43], group jobskills training, and social prescribing [40] there is generally little understanding of the underlying mechanism of effect, limiting efforts to replicate and scale-up successful practices.…”
Section: Introductionmentioning
confidence: 99%
“…While some interventions have shown promise for adults of working age, such as workplace-based stress management [42], co-located welfare advice [43], group jobskills training, and social prescribing [40] there is generally little understanding of the underlying mechanism of effect, limiting efforts to replicate and scale-up successful practices. Interventions are often complex combinations of components, diverse in both form and function [41]. At present, our knowledge of the full range of interventions currently being delivered within local communities is limited, with systematic evidence reviews generally only reporting comprehensively evaluated interventions.…”
Section: Introductionmentioning
confidence: 99%